Thymus size and its correlates among children admitted with severe acute malnutrition: a cross-sectional study in Uganda - Nicolette Nabukeera-Barungi; Betty Lanyero; Benedikte Grenov; Henrik Friis; Hanifa Namusoke; Ezekiel Mupere; Kim F. Michaelsen; Christian Mølgaard; Maria Wiese; Dennis S. Nielsen; Musemma K. Mohammed; Vibeke B. Christensen; et al. (BMC, 2021)
Abstract Background Malnutrition continues to be a major cause of mortality and morbidity among children in resource limited settings. Children with severe acute malnutrition (SAM) experience severe thymus atrophy, possibly reflecting poor immune function. This immune dysfunction is responsible for the severe infections they experience which lead to mortality. Since their immune dysfunction is not fully understood and there has been a lapse in research in this field, more research is needed. Knowing the correlates of thymus size may help clinicians identify those with more severe atrophy who might have more severe immune impairment. We aimed to describe thymus size and its correlates at admission among children hospitalized with SAM. Methods This cross-sectional study involved children 6-59 months admitted with complicated SAM in Mulago National Referral Hospital. Well-nourished children from same communities were used as a community reference group for thymus size. At admission, thymus size was measured by ultrasound scan. Demographic, clinical and laboratory variables were identified at admission. A linear regression model was used to determine correlates of thymus size among children with SAM. Results Among 388 children with SAM, the mean age was 17±8.5 months and 58% were boys. The mean thymus size was 3.14 (95% CI 2.9; 3.4) cm2 lower than that of the 27 healthy community reference children (1.06 vs 4.2 cm2, p<0.001) when controlled for age. Thymus size positively correlated with current breastfeeding (0.14, 95% CI 0.01, 0.26), anthropometric measurements at admission (weight, length, mid-upper-arm circumference, weight-for-height Z scores and length-for-age Z scores) and suspected tuberculosis (0.12, 95% CI 0.01; 0.22). Thymus size negatively correlated with > 2 weeks duration of sickness (-0.10; 95% CI -0.19; -0.01). Conclusion The thymus is indeed a barometer for nutrition since all anthropometric measurements and breastfeeding were associated with bigger thymus. The immune benefits of breastfeeding among children with SAM is underscored. Children with longer duration of illness had a smaller thymus gland indicating that infections have a role in the cause or consequence of thymus atrophy.